Vietnam - Thompson, C Michele (Acquiring Cross-Cultural Competence: Four Stages for Students of French vol I., 1998)
Keywords: dept.his

Book Review: Chinese Acupuncture [l'Acuponcture Chinoise: La Tradition chinoise classifiée, precisée]. (Paris: Maloine, 1972). By George Soulié de Morant. Translated by Lawrence Grinnell, Claudy Jeanmougin and Maurice Leveque. Edited by Paul Zmiewski. Brookline, Mass.: Paradigm Publications, 1994. xxxii, 896 pp. $125.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800040171/resource/name/firstPage-S0021911800040171a.jpg
Keywords: book.review; dept.his

Book Review: Sexual Attraction and Childhood Association: A Chinese Brief for Edward Westermarck. By Arthur P. Wolf. Stanford, Calif.: Stanford University Press, 1995. xxiii, 561 pp. $65.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS002191180002934X/resource/name/firstPage-S002191180002934Xa.jpg
Keywords: book.review; dept.his

Book Review: Essays Into Vietnamese Pasts. Edited by K. W. Taylor and John K. Whitmore. Ithaca, N.Y.: Southeast Asia Program, Cornell University Press, 1995. 288 pp. $20.00 (paper). - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800029971/resource/name/firstPage-S0021911800029971a.jpg
Keywords: book.review; dept.his

Race and the Land in South Africa: African Challenges to Land Policy and Segregation Between 1905 and 1936. - Feinberg, Harvey M. (1999)
Keywords: dept.his; faculty_collection; sabbatical_report

[Biography of Connecticut Governor Ella T. Grasso] - Purmont, Jon E. (Fall;History., 1999)
Keywords: dept.his; faculty_collection; sabbatical_report

[Doctoral Dissertation Revision] - Kalk, Bruce H. (Fall;History., 1998)
Keywords: dept.his; faculty_collection; sabbatical_report

To Cope with a Bad Global Image: Human Rights in the People's Republic of China,1993-1994. - Lee, Ta-ling (Fall;History., 1996)
Keywords: dept.his; faculty_collection; sabbatical_report

History of the American Women's Hospitals in the early 20th century. - Quiroga, Virginia Anne Metaxas (1996)
Keywords: dept.his; faculty_collection; sabbatical_report

Land ownership, African agriculture and politics in South Africa, 1913-1939. - Feinberg, Harvey M. (1992)
Keywords: dept.his; faculty_collection; sabbatical_report

Processus Bernardi Delitiosi: The Trial of Fr. Bernard Delicieux, 3 September - 8 December 1319. - Friedlander, Alan (1991)
Keywords: dept.his; faculty_collection; sabbatical_report

Book Research and Testimony Before the House Subcommittee on International Law and Immigration and Refugees, October 2, 1991. - Hamilton-Merritt, Jane (1991)
Keywords: dept.his; faculty_collection; sabbatical_report

Seeds of Empire: The American Revolutionary Conquest of the Iroquois - Mintz, Max M. (University, 1999)
"The American Revolution was a struggle not only for independence, but for the lands of Native Americans. The jewel in this conflict was the upstate New York domain of the Iroquois Six Nations, where fertile river valleys were a magnet for farmers weary of New England's stubborn soil." "While at first intentionally neutral, the Iroquois were soon forced to choose sides between either rebel or British forces. Seeds of Empire recreates the events surrounding General John Sullivan's scorched-earth campaign against the Six Nations of the American Indians of New York and the Eastern territories in 1779, following the surrender of General John Burgoyne's entire British army at the Battle of Saratoga. Abandoned by both the rebels and the British at the end of the revolution and devastated by the ravages of war, the Iroquois found themselves powerless to resist the post-Revolutionary takeover and peopling of their heartland by the new American nation."–Jacket.
Keywords: Sullivan's Indian Campaign; 1779; dept.his; faculty_collection

Leonard Bacon: New England Reformer and Antislavery Moderate - Davis, Hugh (Louisiana State University Press, 1998)
A nationally powerful reformer, editor, church leader, and author, Leonard Bacon (1802-1881) influenced the thinking of northern Protestants for more than fifty years. In this detailed biography, Hugh Davis offers the first scholarly treatment of Bacon's life and work. Convinced that he was obligated to educate the American people on a broad range of social, political, and theological issues, Bacon, a Congregational minister, actively sought to connect his church and community to the larger world of organized benevolence, religious and reform journalism, social activism, and scholarship. The son of New England Congregational missionaries to the native Americans on the Michigan frontier, he also endeavored to extend evangelical religion and New England ideas and institutions to the rest of the nation and even overseas. Offering new insights into the nineteenth-century Protestant ministry, the evangelical mentality, and the efforts of Americans in Bacon's generation to address the moral and social issues of their time, Leonard Bacon will prove an invaluable contribution to American religious, social, and political history.–(Source of description unspecified.)
SCSU Faculty Scholar Award
Keywords: Bacon; Leonard; 1802-1881; Congregational churches; Biography; Clergy; United States; award_winner; dept.his; faculty_collection

Racism Matters - Wright, W. D. (Praeger, 1998)
This work offers a discussion of racism in America focusing on how white people have been affected by their own racism and how it impacts upon relations between blacks and whites. It draws attention to how racism is different from race and shows how whites have maintained a white racist America.
Keywords: Race relations; Racism; United States; United States; dept.his; faculty_collection

A Concise History of the United States with Documents - House, Lewis; Purmont, Jon E.; Leonard, Ira M. (TLI Press, 1997)
Keywords: History; United States; dept.his; faculty_collection

Black Intellectuals, Black Cognition, and a Black Aesthetic - Wright, W. D. (Praeger, 1997)
Keywords: African American intellectuals; African Americans; Intellectual life; African American aesthetics; African Americans; Race identity; dept.his; faculty_collection

Processus Bernardi Delitiosi: The Trial of Fr. Bernard Délicieux, 3 September-8 December 1319 - Friedlander, Alan (American Philosophical Society, 1996)
Keywords: Bernard; Délicieux; frère; approximately 1260-approximately 1320; Trials; litigation; etc; dept.his; faculty_collection

Portrait of an Unknown Man: Manuel Azaña and Modern Spain - Rivas Cherif, Cipriano de; Stewart, Paul; Rivas, Enrique de (Fairleigh Dickinson University Press ; Associated University Presses, 1995)
Keywords: 1931-1939; Azaña; Manuel; 1880-1940; Presidents; Biography; Spain; Politics and government; Spain; dept.his; faculty_collection

A Concise History of the United States. - House, Lewis; Purmont, Jon E.; Leonard, Ira (TLI Press, 1994)
Keywords: History; United States; dept.his; faculty_collection

The Bamboo Gulag: Human Rights in the People's Republic of China, 1991-1992 - Lee, Ta-ling; Copper, John Franklin (University of Maryland School of Law, 1994)
Keywords: 1976-2002; China; China; China; Civil rights; Human rights; Politics and government; dept.his; faculty_collection

Tragic Mountains: The Hmong, the Americans, and the Secret Wars for Laos, 1942-1992 - Hamilton-Merritt, Jane (Indiana University Press, 1993)
Keywords: 20th century; 20th century; Laos; Government policy; History; Hmong (Asian people); Laos; Hmong (Asian people); Politics and government; Laos; Wars; Hmong (Asian people); dept.his; faculty_collection

Failure of Democracy Movement: Human Rights in the People's Republic of China, 1988/89 - Lee, Ta-ling; Copper, John Franklin (School of Law, University of Maryland, 1991)
Keywords: China; China; China; Civil rights; History; Human rights; Tiananmen Square Incident; 1989; dept.his; faculty_collection

Joshua Leavitt, Evangelical Abolitionist - Davis, Hugh (Louisiana State University Press, 1990)
Keywords: 1815-1861; United States; 19th century; United States; Biography; Antislavery movements; History; Leavitt; Joshua; 1794-1873; Abolitionists; Social conditions; To 1865; United States; United States; Evangelicalism; dept.his; faculty_collection

The Generals of Saratoga: John Burgoyne and Horatio Gates - Mintz, Max M. (Yale University Press, 1990)
Keywords: Burgoyne; John; 1722-1792; Gates; Horatio; 1728-1806; Saratoga Campaign; N.Y.; 1777; dept.his; faculty_collection

Plenty of barbarians, but no bird's milk: The depiction of Russia in German school books, 1890-1914 - Paddock, Troy R. E. (Internationale Schulbuchforschung, 1998)
This article examines the description of Russia in German history and geography textbooks. Nineteenth-century German pedagogical theory linked the natural sciences and the human sciences; the connection supplies further evidence of the perceived organic nature of the nation-state. Although regional and confessional differences among the German states affected the description of German history, the depiction of Russia was consistent. Russia was depicted as a barbaric, backward, and Asiatic empire. The implicit, and often explicit, comparison in the texts was between Russia and Germany. The description of a foreign power served to reinforce German national identity. Moreover, an examination of German geography and history textbooks reveals striking similarities between the perception of Russia in Germany and the Anglo-French depiction of the Near East. Dieser Aufsatz befaßt sich mit dem Rußlandbild in deutschen Schulbüchern für Geschichte und Geographie. Deutsche Pädagogik im 19. Jahrhundert verband die Naturwissenschaft mit der Geisteswissenschaft; diese Verbindung ist noch ein Beweis für die Auf- fassung des Nationalstaats als organisches Wesen. Obwohl regionale und konfessionelle Unterschiede unter den deutschen Ländern die Darstellung von deutscher Geschichte beeinflußten, war die Schilderung von Rußland übereinstimmend. Rußland wurde als ein barbarisches, rückständiges, asiatisches Reich gezeichnet. Der unausgesprochene, und manchmal doch ausgesprochene Vergleich in den Büchern galt Deutschland und Rußland. Die Darstellung der fremden Macht verstärkte die deutsche Nationalidentität. Außerdem enthüllt eine Untersuchung der Schulbücher überraschende Ähnlichkeiten zwischen der deutschen Beschreibung von Rußland und den englischen und französischen Darstellungen des Nahen Osten. L'auteur de cet article analyse l'image de la Russie dans les manuels scolaires allemands d'histoire et de géographie. La pédagogie allemande du 19ème siècle faisait le lien entre les sciences naturelles et les sciences humaines; cette association fournit une preuve supplémentaire du fait que l'Etat-nation était perçu comme un organisme vivant. Alors que les différences régionales et confessionnelles existant entre les différents Etats allemands influençaient la présentation de l'histoire allemande, la description de la Russie était concordante. La Russie était dépeinte comme un empire barbare, arriéré et asiatique. La comparaison implicite, et souvent explicite des textes scolaires concernait la Russie et l'Allemagne. La représentation d'une puissance étrangère servait à renforcer l'identité allemande. En outre, l'analyse de ces manuels révèle des ressemblances étonnantes entre la perception de la Russie et les portraits français et anglais du Proche-Orient.
Keywords: dept.his; ⛔ No DOI found

Abolition and Antislavery: United States - Forbes, Robert P. (A Historical Guide to World Slavery, 1998)
Eminent scholars provide an overview of what we now know about slavery as an institution and way of life in cultures around the globe from ancient times to the present day. Drawing on the virtual explosion of empirical research and theoretical discussion on the subject over the past thirty years, many of the articles overturn conventional wisdom and illuminate little-known aspects of the subject, with essays on topics such as concubinage, eunuchs, and occupational mobility.
Keywords: dept.his

Slavery and the Evangelical Enlightenment - Forbes, Robert Pierce (Religion and the Antebellum Debate Over Slavery, 1998)
Keywords: 19th century; 19th century; Slavery; History; History / United States / 19th Century; Slavery and the church; Social Science / Ethnic Studies / African American Studies; Social Science / Sociology of Religion; United States; dept.his; faculty_collection

Francis Kernan: The Life and Times of a 19th Century, Citizen-Politician of Upstate New York - Kernan, Karen Clemens; Kernan, John Devereux; Forbes, Robert P. (Oneida County Historical Society, 1999)
Keywords: dept.his

Book Review: Michael r. dutton, policing and punishment in china , london and new york: cambridge university press, 1992. pp. xii, 391. 74.95 (ISBN 0-521-40097-X). - Lee, Taling; Dutton, Michael R (Law and History Review, 1996)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/011-205-443-787-032 tex.type: [object Object]
Keywords: book.review; dept.his

A social history of wet nursing in America: From breast to bottle. - Metaxas, VA (Isis, 1999)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000085890500069
Keywords: dept.his

Ghaylan Al-Dimashqi: The isolation of a heretic in Islamic historiography - Judd, SC (International Journal of Middle East Studies, 1999)
7 citations (Crossref) [2023-10-31] tex.organization: Middle E Studies Assoc tex.unique-id: ISI:000080330000002 29th Annual Meeting of the Middle-East-Studies-Association, WASHINGTON, D.C., DEC 06-10, 1995
Keywords: dept.his

Book Review: War and the illiberal conscience: coker, christopher: boulder: westview press 240 pp., publication date: april 1998 - Paddock, Troy (History: Reviews of New Books, 1999)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/076-456-415-896-519 tex.type: [object Object]
Keywords: book.review; dept.his

The Carswell affair: The politics of a Supreme Court nomination in the Nixon administration - Kalk, BH (American Journal of Legal History, 1998)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/107-015-379-096-504 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.his

Book Review: Barbara Caine. English Feminism, 1780–1980 . New York: Oxford University Press. 1997. Pp. xvii, 336. 19.95 paper. ISBN 0-19-820434-5. - Beals, Polly (Albion, 1998)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/191-041-092-429-055 tex.type: [object Object]
Keywords: book.review; dept.his

Still stuck at sevastopol: the depiction of russia during the russo-japanese war and the beginning of the first world war in the german press - Paddock, Troy (German History, 1998)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/111-569-153-315-152 tex.type: [object Object]
Keywords: dept.his

The machine in the nursery: incubator technology and the origins of newborn intensive care. - Quiroga, VAM (Isis, 1997)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000071450400068
Keywords: dept.his

Revolutionary outlaws - allen,ethan and the struggle for independence on the early american frontier - bellesiles,ma - Mintz, MM (American Historical Review, 1995)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1995RJ06900100
Keywords: dept.his

South Africa and land ownership: what's in a deed? - Feinberg, Harvey M (History in Africa, 1995)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-416-240-180-454 tex.type: [object Object]
Keywords: dept.his

Book Review: Battles of the Revolutionary War, 1775–1781. By W. J. Wood. (Chapel Hill: Algonquin, 1990. xxxii + 315 pp. $24.95.) - Mintz, Max M. (Journal of American History, 1991)
Max M. Mintz; Battles of the Revolutionary War, 1775–1781. By W. J. Wood. (Chapel Hill: Algonquin, 1990. xxxii + 315 pp. $24.95.), Journal of American History,
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1991GF12400029 tex.unique-id: [object Object]
Keywords: book.review; dept.his

Save the babies - american public-health reform and the prevention of infant-mortality, 1850-1929 - meckel,ra - Quiroga, VAM (Journal of American History, 1991)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1991FP54300084
Keywords: dept.his; peer-reviewed

Diphtheria and medical therapy in late 19th century New York City - Quiroga, V.A.M. (New York State Journal of Medicine, 1990)
Keywords: Diphtheria; History of Medicine; 19th Cent.; Human; Intubation; Intratracheal; New York City; Portraits; Tracheotomy; article; dept.his; diphtheria; history of medicine; human; priority journal; ⛔ No DOI found

Book Review: abolitionism: A revolutionary movement, by hugh davis - Davis, Hugh (Pennsylvania Magazine of History and Biography, 1990)
Citation Key Alias: lens.org/165-049-126-830-503 tex.type: [object Object]
Keywords: book.review; dept.his; ⛔ No DOI found

Book Review: Denis Lalande, Jean II le Meingre, dit Boucicaut (1366–1421): Etude d'une biographie héroïque . (Publications romanes et françaises, 184.) Geneva: Droz, 1988. Paper. Pp. ii, 227. - Friedlander, Alan (Speculum, 1990)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/157-761-815-103-415 tex.type: [object Object]
Keywords: book.review; dept.his